Cortical and white matter mapping in the visual system-more than meets the eye: on the importance of functional imaging to understand visual system pathologies - Raz, Noa; Levin, Netta (Frontiers in integrative neuroscience, 2014)
Information transmission within the visual system is highly organized with the ultimate goal of accomplishing higher-order, complex visuo-spatial and object identity processing. Perception is dependent on the intactness of the entire system and damage at each stage-in the eye itself, the visual pathways, or within cortical processing-might result in perception disturbance. Herein we will review several examples of lesions along the visual system, from the retina, via the optic nerve and chiasm and through the occipital cortex. We will address their clinical manifestation and their cortical substrate. The latter will be studied via functional magnetic resonance imaging (fMRI) and Diffusion Tensor Imaging (DTI), enabling cortical, and white matter mapping of the human brain. In contrast to traditional signal recording, these procedures enable simultaneous evaluation of the entire brain network engaged when subjects undertake a particular task or evaluate the entirety of associated white matter pathways. These examples provided will highlight the importance of using advanced imaging methods to better understand visual pathologies. We will argue that clinical manifestation cannot always be explained solely by structural damage and a functional view is required to understand the clinical symptom. In such cases we recommend using advanced imaging methods to better understand the neurological basis of visual phenomena.